Numerical Assessment of the Influence of Process and Geometric Parameters on Extrusion Welds and Die Deformation after Multiple-cycles. (2015) - Pinter, Tommaso; Reggiani, Barbara; Donati, Lorenzo; Tomesani, Luca
Abstract: A comprehensive investigation on the correlation between die design and process parameters with extrusion welds (seam and charge) prediction and die deformation after multiple-cycles is presented. In particular, the influence of the number of legs (2, 3 and 4) as well of some commonly adopted industrial best design practices in the extrusion of a round tube profile are examined by the ALE code HyperXtrude® for the AA6005A alloy. Then, for the same three designs, the die deformation after multiple-cycles is computed by applying a developed user sub-routine that account for the pressure and temperature maps and for the dwell-time that represents the time required to extrude each single billet. A sensitivity analysis on the influence of process parameters (ram speed, billet length and alloy) on the achieved die deformation after a fixed extruded amount is also performed.